PRINSIP AL-TAYSÄªR DALAM FIQH AL-AQALLIYÄ€T YÅªSUF AL-QARAá¸ŒÄ€WÄª - Khalil, Abdul Wahab (IAIN Kediri, 2016)
The Muslim minorities in the West who are currently dealing with a multitude of problem receives attention from Muslim scholars. Syaikh YÃ…Â«suf al-QaraÃ¡Â¸ÂÃ„ÂwÃ„Â« is the first Muslim scholar who attempted to provide a solution to the problems, especially related to the implementation of religious teachings, as he outlined it in the framework of fiqh al-aqalliyÃ„Ât. In principle, this is not something new in Islamic jurisprudence, because its legal sources are still the same. Nevertheless, this kind of fiqh is different in the sense that it does not merely talk about legal issues, but also the problems of theology and morals that the Muslim minorities in the West are currently dealing with in their relations with non-Muslims. Fiqh al-aqalliyyÃ„Ât is also characterized by the use of the principle of al-taysÃ„Â«r as clearly prominent in the fatwÃ„Âs by Syaikh YÃ…Â«suf al-QaraÃ¡Â¸ÂÃ„ÂwÃ„Â«, such as on the validity of both performing Friday prayer in the morning due to limited time for religious sermon (khuÃ¡Â¹Âbah) and during Ã¡Âºâ€œuhr time in some countries. This article will explore further this principle of al-taysÃ„Â«r in the QaraÃ¡Â¸ÂÃ„ÂwÃ„Â«Ã¢â‚¬â„¢s fiqh al-aqalliyyÃ„Ât. Keywords: YÃ…Â«suf al-QaraÃ¡Â¸ÂÃ„ÂwÃ„Â«, Fiqh al-AqalliyÃ„Ât, al-TaysÃ„Â«r